Ten-Year Single Institutional Analysis of Geographic and Demographic Characteristics of Patients Treated With Stereotactic Body Radiation Therapy for Localized Prostate Cancer - Aghdam, Nima; Carrasquilla, Michael; Wang, Edina; Pepin, Abigail N.; Danner, Malika; Ayoob, Marilyn; Yung, Thomas; Collins, Brian T.; Kumar, Deepak; Suy, Simeng; Collins, Sean P.; Lischalk, Jonathan W. (Frontiers in Oncology, 2021)
Objectives: Stereotactic Body Radiation Therapy (SBRT) for prostate cancer has comparable efficacy and toxicity to conventionally fractionated radiotherapy. Decreasing the number of treatments from forty to five may ease treatment burden and increase accessibility for logistically challenged patients. Travel distance is one factor that affects a patient's access to treatment and is often related to geographic location and socioeconomic status. In this study, we review the demographic and geographic factors of patients treated with SBRT for prostate cancer from a single institution. Methods: Patient zip-codes from 1035 patients were derived from a prospectively maintained quality-of-life database for prostate cancer patients treated with SBRT from 2008-2017. The geospatial distance between the centroid of each zip-code to our institution was calculated using the R-package Geosphere. Characteristics for 721 patients were evaluated at the time of analysis including: race, age, and insurance status. To assess the geographic reach of our institution, we evaluated the demographic features of each zip-code using US Census data. Statistical comparisons for these features and their relation to distance traveled for treatment was performed using the Mann-Whitney U test. Finally, an unsupervised learning algorithm was performed to identify distinct clusters of patients with respect to median income, racial makeup, educational level, and rural residency. Results: Patients traveled from 246 zip-codes at a median distance of 11.35 miles. 40% of patients were African-American, 6.9% resided in a rural region, and 22% were over the age of 75. Using K-means cluster analysis, four distinct patient zip-code groups were identified based on the aforementioned demographic features: Suburban/high-income (45%), Urban (30%), Suburban/low-income (17%), and Rural (8%). For each of the clusters, the average travel distance for SBRT was significantly different at 11.17, 9.26, 11.75 and 40.2 miles, respectively (p-value:<0.001). Conclusions: Distinct demographic features are related to travel distance for prostate SBRT. Despite longer travel distance, a small but significant rural cohort can access this new technology. Travel distance did not prevent uptake of SBRT in our large African-American and elderly population. Prostate SBRT offers a modern treatment to a diverse population and particularly for those who live significant distances from a treatment center.